Upper extremity injuries in golf - Bayes, M. C.; Wadsworth, L. T. (The Physician and Sportsmedicine, 2009)
Golf is an asymmetric sport with unique patterns of injury depending upon the skill level. Higher handicap players typically experience injuries that result from swing mechanics, whereas lower handicap and professional players have overuse as the major cause of their injuries. The majority of shoulder injuries affecting golfers occur in the nondominant shoulder. Common shoulder injuries include subacromial impingement, rotator cuff pathology, glenohumeral instability, and arthritis involving the acromioclavicular and/or glenohumeral joints. Lead arm elbow pain resulting from lateral epicondylosis (tennis elbow) is the leading upper extremity injury in amateur golfers. Tendon injury is the most common problem seen in the wrist and forearm of the golfer. Rehabilitation emphasizing improvement in core muscle streng is important in the treatment of golf injury. Emerging treatments for tendinopathy include topical nitrates, ultrasound-guided injection of therapeutic substances, and eccentric rehabilitation. There is evidence supporting physiotherapy, and swing modification directed by a teaching professional, for treatment of upper extremity golf injuries. This article focuses on upper extremity injuries in golf, including a discussion of the epidemiology, causes, diagnosis, treatment, and prevention of injuries occurring in the shoulder, elbow, wrist, and hand.